Women and Ecosystems - Webb, Jena (Amazon Frontlines, 2019)
Over the centuries many parallels have been drawn between women and the earth, starting with the age-old (and, for some, contested) Mother Earth, or Pachamama. More recently, the destruction of the earth for natural resource extraction has been compared with and attributed to the same underlying patriarchal forces as violence against women. Correspondingly, research has shown that environmentalism is perceived as un-masculine (Brough et al. 2016) and even that men are less likely to recycle than women because they are worried people will think they’re homosexual.
Keywords: 2000 à aujourd'hui; amérique latine; amériques; approches et analyses; autonomisation; invisibilités; inégalités; militance; mouvements des femmes*; patriarcat; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; écoféminisme; équateur